Megasphaera elsdenii and Saccharomyces cerevisiae as direct fed microbials and their impact on ruminal microbiome during an acute acidosis challenge in continuous culture - Arce Cordero, José Alberto (2023)
Our objective was to evaluate the effects of combinations of Saccharomyces cerevisiae and Megasphaera elsdenii as direct fed microbials (DFM) on ruminal microbiome during an acute acidosis challenge in a continuous culture system. Treatments provided a DFM dose of 1 × 108 colony-forming unit (CFU)/mL, as follows: Control (no DFM); YM1 (S. cerevisiae and M. elsdenii strain 1); YM2 (S. cerevisiae and M. elsdenii strain 2); and YMM (S. cerevisiae and half of the doses of M. elsdenii strain 1 and strain 2). We conducted 4 experimental periods of 11 d, which consisted of non-acidotic days (1–8) and acidotic challenge days (9–11) to establish acute ruminal acidosis conditions with a common basal diet containing 12% NDF (neutral detergent fiber) and 58% starch. Treatments were applied from days 8–11, and samples of liquid and solid associated bacteria collected on days 9–11. Overall, 128 samples were analyzed by amplification of the V4 region of bacterial 16S rRNA, and data were analyzed with R and SAS for alpha and beta diversity, taxa relative abundance, and correlation of taxa abundance with propionate molar proportion. We observed a lower bacterial diversity (Shannon index, P = 0.02) when YM1 was added to the diet in comparison to the 3 other treatments. Moreover, compared to control, addition of YM1 to the diet increased relative abundance of phylum Proteobacteria (P = 0.05) and family Succinivibrioceae (P = 0.05) in the solid fraction and tended to increase abundance of family Succinivibrioceae (P = 0.10) and genus Succinivibrio (P = 0.09) in the liquid fraction. Correlation analysis indicated a positive association between propionate molar proportion and relative abundance of Proteobacteria (r = 0.36, P = 0.04) and Succinivibrioceae (r = 0.36, P = 0.05) in the solid fraction. The inclusion of YM1 in high grain diets with a high starch content resulted in greater abundance of bacteria involved in succinate synthesis which may have provided the substrate for the greater propionate synthesis observed.